Edukasi Peduli Lingkungan sebagai Upaya Pencegahan Bencana Banjir di Kelurahan Sumarorong Kabupaten Mamasa Sulawesi Barat - Karim, Faradilah Farid (Universitas Negeri Gorontalo, 2024)
Sumarorong District is one of the areas in Mamasa Regency that often experiences flood disasters. It was recorded that in 2012 there was a flash flood which not only caused damage to infrastructure but even caused casualties. In 2019 Sumarorong District was again hit by flash floods and landslides which resulted in three elementary schools experiencing serious damage. The flood was triggered by the Batanguru River which divides Sumarorong District in this area overflowing, submerging settlements along the river mouth. The problem of flooding in this area is caused by several factors, such as the rampant illegal logging of forests to convert them into plantation areas and the accumulation of rubbish in river basins. If waste is not managed properly it will cause environmental problems such as pollution, blockage of drainage channels and even flooding. Apart from that, it can also have a negative impact on the health of the surrounding community. The aim of this program is to provide education regarding the importance of awareness in protecting the environment as an effort to prevent flood disasters in Sumarorong District. Through this service activity, it is hoped that it can increase community awareness in preserving forests and managing household waste more independently and sustainably.